How customers cope with service failure? A study of brand reputation and customer satisfaction - Sarkar Sengupta, Aditi; Balaji, M.S.; Krishnan, Balaji C. (Journal of business research, 2015)
In this paper we examine the different coping mechanisms used by customers when they confront service failure. It was found that the coping mechanism used by customers changes depending on the severity of the service failure. Further, it was observed that brand reputation moderates the relationship between severity of service failure and coping strategies, customer satisfaction and behavioral intentions under different conditions. We conducted an experimental study in an airline travel context. The data supports the proposed model.